DOI: HTTPS://DOI.ORG/10.36873/A , MAHDI SANTOSO, YANCILUK: PENGARUH EKSTRAKSI AIR PANAS DAN N-HEKSANA TERHADAP KARAKTERISTIK BAHAN BAKU DAN SIFAT REKAT PAPAN PARTIKEL PELEPAH NIPAH - Agrienvi (Agrienvi, Jurnal Ilmu Pertanian, 2019)
ABSTRACTNipa (Nypa fruticans Wurmb) is a non wood lignosellulosic materials that potential as raw material of compositeboard. One of disadvantage of the nipa fronds was contains are very high extractives and inorganic substances. Thepresence of high content of extractives in raw material of particle board potentially be an obstacle in the process ofgluing the composite board. The existing of extractive substances on the surface of the composite board raw materialscontribute to make the bonding process is not going well. On the other side, the utilization of natural binder for nonwood composite is still limited. This research focused to investigated the effects of extractive subtances for bondingperformance of natural binder such as citric acid for nipa fronds particleboard. The particles screened passed throughaperture sizes of 10 mesh and treated with three condition (non extraction, hot water extraction and n -hexanaextraction) were used as materials in this research. Addition of natural binder of 10% based on air dried particles wasdone and pressing temperature was set at 180ºC under a pressure of 3,6 MPa during 10 minutes. The physics andmechanics properties of particleboard was tested by standard JIS A 5908:2003. The results showed that theextractiction treatments for raw material affects on the properties of the particleboards. Hot water extraction treatmentwas able to give the best results. The properties of particleboard was density 0.84 g.cm-3; moisture content 7.44%;thickness swelling 1,12%; water absorption 21,83%; surface roughness 7.57 ?m; internal bonding 0.49 MPa; modulusof rupture 10.42 MPa and modulus of elasticity 3.65 GPa. All of the properties of nipa fronds particleboard meet mostof the standards JIS A 5908:2003.Keywords: Hot water extraction, n-hexane extraction, nipa frond particleboard, natural binder, citric acid.